Sorjan Farming: A Sustainable Solution for Climate Resilience in Coastal Bangladesh - Ahmed, Sharif; Debnath, Manik; Bhandari, Humnath (International Rice Research Institute, 2024)
The smallholder farmers of Bangladesh are facing huge challenges related to climate change. In coastal areas, especially southern Bangladesh, soil salinity in the dry season, and high-frequency rainfall in the wet season result in frequent flooding along with less irrigation water available during the dry season are the major agricultural constraints. The sorjan farming method is an effective way for farmers to cultivate year-round vegetables and produce fish together under these adverse ecological and climatic conditions.